MORPHOLOGY AND ORIGIN OF FOLDING IN THE SOUTH TIEN SHAN - Rogozhin E.A. (My University, 2004)
The qualitative and quantitative analysis of the holomorphic folding morphology in the central segment of the South Tien Shan revealed its heterogeneity in the Paleozoic rock sequences. Against the background of the gradual folding simplification from the axial parts of the mountain system to its periphery, the relatively intense dislocations alternate with less tense structural fields. The former are restricted to the anticlinoria and large anticlines, the latter, to the synclinoria and large synclines. The study of the fold formation history proved the fact that the recent orogenic structures had been inherited from the anticlinoria and synclinoria of Hercynian time. The disharmonic and highly variable folding of the South Tien Shan seems to have originated as a result of the combined effects of three factors: (1) the deformation of the allochthone rocks during the gravitational movement of the tectonic nappes; (2) the external subhorizontal reduction of the crystalline basement and the overlying volcanic and sedimentary rock sequences, and (3) advective movements in the rocks of the sedimentary cover.
Keywords: FOLDING MORPHOLOGY; SOUTH TIEN SHAN; SYNCLINORIA; STRUCTURAL FIELDS; Paleozoic; Paleozoic; Палеозой